História dos grupos escolares em Garibaldi e Farroupilha: matizes de práticas pedagógicas e escolares (Rio Grande do Sul, 1926-1949) - Fernandes, Cassiane Curtarelli (My University, 2022)
The thesis has as its investigation object the history of school groups established in two municipalities located in Rio Grande do Sul. Its objective is to investigate the constitution and organization of school groups in Garibaldi and Farroupilha, narrating nuances of school cultures produced in the daily life of these institutions in correlation with the context. The temporal delimitation begins in 1926, as it was the year of the first school group?s installation in Garibaldi, and ends in 1949, due to the possible transference of Daltro Filho School Group and the changes that occurred in the local schooling process over the next decade, with the creation of municipal school groups in Garibaldi. The theoretical contribution is based on Cultural History, History of Education and History of School Institutions. The methodology used was historical document analysis and Oral History. The study prioritized pedagogical and school practices as a category of analysis, understood as the ordinary activities of the class and also of the school; thus distinct from other social practices produced and reproduced in everyday school life, with the task of teaching, educating, disciplining, moralizing, guiding. Therefore, the thesis is that local school groups were constituted as privileged spaces for the dissemination of national culture, especially through the organization and realization of civic festivities. In this scenario, I highlight Grupo Escolar Farroupilha?s performance as a reference school for others, especially in the development of nationalization practices and in relation to their teacher?s work, who went beyond the classroom, occupying prominent places in the educational area; training other teachers through improvement courses. I argue that, in local school groups, there was a circulation of practices linked to the process of educational renewal in Rio Grande do Sul with the use of reading and writing books, materials and spaces that were related to intuitive teaching and the simultaneous method. However, at the same time, there was a continuity of practices that were opposite to this discourse, such as the application of physical punishment and humiliation, which are filed only in students and teachers memories. Also, when looking at the failure rates up to the end of the 1940s, I think that the educational renewal discourse in vogue was not efficient to the point of intervening in the reality of these institutions, fact that contributed to school groups being places of rigor, selections and exclusions. Finally, I defend the importance of the faculty who attended each of the schools surveyed, assuming, in the face of certain omission by the State, the leading role in the search for solutions to everyday problems. The teachers, together with students and communities, created and recreated daily life, devising practices for resources acquisition that would bring more comfort to students. I point out that they were the ones who resisted and recreated practices that were not in the legislation and educational discourses in circulation. In the subtlety of everyday practices, not everything was accepted or put into effect. [resumo fornecido pelo autor]
A tese tem como objeto de investigação a história dos grupos escolares instituídos em dois municípios localizados no Rio Grande do Sul. Seu objetivo é investigar a constituição e a organização dos grupos escolares em Garibaldi e Farroupilha, narrando nuances das culturas escolares produzidas no cotidiano destas instituições em correlação com o contexto. A delimitação temporal inicia em 1926, por ser o ano de instalação do primeiro grupo escolar em Garibaldi, e finaliza em 1949, em virtude da possível transferência do Grupo Escolar Daltro Filho e das mudanças ocorridas no processo de escolarização local durante a próxima década, com a criação de grupos escolares municipais em Garibaldi. O aporte teórico fundamenta-se na História Cultural, na História da Educação e na História das Instituições Escolares. A metodologia utilizada foi a análise documental histórica e a História Oral. O estudo privilegiou como categoria de análise as práticas pedagógicas e escolares, entendidas como os fazeres ordinários da classe e também da escola; distintas, assim, de outras práticas sociais produzidas e reproduzidas na tessitura do cotidiano escolar, com a tarefa de ensinar, educar, disciplinar, moralizar, orientar. Portanto, a tese é a de que os grupos escolares locais se constituíram como espaços privilegiados para a disseminação da cultura nacional, sobretudo a partir da organização e da realização das festividades cívicas. Neste cenário, destaco a atuação do Grupo Escolar Farroupilha como uma escola de referência para as demais, inclusive na elaboração de práticas de nacionalização, colocando em evidência o trabalho de um corpo docente que alçou voos para além da sala de aula, ocupando lugares de destaque na área educacional; formando, inclusive, outros professores por meio de cursos de aperfeiçoamento. Defendo que, nos grupos escolares locais, houve uma circulação de práticas vinculadas ao processo de renovação educacional no Rio Grande do Sul com o uso dos livros de leitura e escrita, de materiais e espaços que se relacionavam ao ensino intuitivo e ao método simultâneo. No entanto, ao mesmo tempo, houve uma continuidade de práticas que se distanciavam deste discurso, como a aplicação de castigos físicos e humilhações, arquivadas apenas nas lembranças de alunos(as) e professoras. Também, ao olhar para os índices de reprovação até o final da década de 1940, penso que o discurso de renovação educacional em voga não foi eficiente ao ponto de intervir na realidade destas instituições, contribuindo para que fossem lugares de rigorosidades, seleções e exclusões. Por fim, defendo a importância do corpo docente que esteve em cada uma das escolas pesquisadas, assumindo, diante de certa omissão do Estado, o protagonismo na busca de soluções para os problemas cotidianos. As professoras, junto aos alunos e as comunidades, criaram e recriaram o cotidiano, inventariando práticas para a aquisição de recursos que trariam mais conforto aos estudantes. Aponto que foram elas que resistiram e recriaram práticas que não estavam na legislação e nos discursos educacionais em circulação. Na sutileza das práticas cotidianas, nem tudo foi aceito ou efetivado. [resumo fornecido pelo autor]
Keywords: Educação - Rio Grande do Sul - História; Ambiente escolar - Garibaldi - Aspectos culturais; Ambiente escolar - Farroupilha - Aspectos culturais; Education - Rio Grande do Sul (Brazil) - History; School environment - Garibaldi (Brazil) - Cultural aspects; School environment - Farroupilha (Brazil) - Cultural aspects